An adaptive neural fuzzy virtual inertia control method for VSC-HVDC system - Zhu, Lin; Liu, Qi; Liu, Shan; Wang, Zhen; Meng, Jianhui; Gu, Likang; Zhou, Zixin (Frontiers in Energy Research, 2023)
Compared to conventional DC transmission, Voltage source converter based high voltage direct current transmission (VSC-HVDC) has the advantages of independently controllable transmission power, no commutation failure, no reactive power compensation and low harmonic levels. However, VSC-HVDC transmission cannot provide effective frequency support and regulation for the system after grid connection. To address this problem an adaptive neural fuzzy virtual inertia control method is proposed to impose a control strategy on the converter at the receiving end of a VSC-HVDC transmission. The method uses the rate of change of frequency and the amount of change of frequency as constraints to dynamically adjust the virtual inertia and damping coefficients. It provides larger inertial support when the frequency fluctuation is large and smaller inertial support when the frequency fluctuation is small, thus adapting to different operating conditions and improving the inertial support capacity and frequency stability of the system. Finally, the proposed control strategy is experimentally verified by hardware-in-the-loop simulation.